APPLICATION OF BASIC PHYSICS CONCEPTS TO THE INTERACTION OF RADIATION WITH MATERIALS IN RADIOLOGICAL EXAMINATIONS - Taslima, Saufa; Pelawi, Awan; Sitohang, Putra Raja P P (Jurnal Ilmiah METADATA, 2023)
This study quantitatively evaluates the application of fundamental physics concepts, namely the attenuation and scattering of ionizing radiation, in diagnostic radiology examinations, with the aim of validating predictions of radiation (X-ray) interactions with various types of biological tissues and phantom materials. Based on the Beer-Lambert theory and scattering model, this study tests the hypothesis that the physical properties of matter (atomic number, density) significantly influence the attenuation and scattering coefficients, which correlate with image quality and dose profiles. Using a quantitative experimental design with 30 phantom and biological samples, radiation intensity measurements were performed with a calibrated detector under controlled acquisition parameters, as well as digital image quality evaluation. The results show a strong correlation between radiation attenuation and atomic number and density of the material (e.g., bone attenuation is 2.5x higher than soft tissue, p < 0.001, d = 1.8), as well as the dominance of Compton scattering which is directly proportional to material thickness and scattering angle. A positive correlation was also found between the scattering/transmission ratio and image artifacts such as beam hardening. In conclusion, an understanding of fundamental physics is crucial for predicting radiation interactions, providing theoretical contributions to accurate simulation models, and providing practical implications for optimizing acquisition parameters, image reconstruction algorithms, and radiation dose management to improve diagnostic quality.